SUSTAINING HERITAGE FOODSCAPES: SOCIO-CULTURAL IMPACTS AND RELATIONAL WELL-BEING IN BANGKOK'S YAOWARAT DISTRICT - WORRACHANANUN, Maneenate (Asian Interdisciplinary and Sustainability Review, 2026)
This qualitative ethnographic study investigates how food tourism reshapes the socio-cultural landscape, everyday practices, and relational well-being within Bangkok’s Yaowarat Street Food District. While Yaowarat is globally recognized for its iconic culinary heritage, the localized, lived impacts of this touristic prominence on host communities remain heavily underexplored. Drawing on year-long fieldwork, 15 in-depth qualitative interviews, 5 focus groups, and 2 dialogue workshops, this research examines the complex negotiations between residents and vendors amid rapid, tourism-driven global change. The findings reveal four primary dynamics: the reconfiguration of temporal and spatial rhythms causing simultaneous pride and fatigue; authenticity enacted as an ongoing, embodied negotiation rather than a fixed cultural attribute; cultural continuity sustained through informal, intergenerational stewardship; and community well-being experienced relationally through spatial familiarity and emotional security. Ultimately, this study argues that sustainable food tourism transcends traditional economic indicators, relying instead on the preservation of everyday rhythms, affective relations, and spatial autonomy. By centering lived experiences within an Asian urban context, this research offers a critical, multidimensional perspective on cultural sustainability and inclusive heritage management in rapidly transforming urban heritage foodscapes.